Desigualdade social na prevalência e nas modalidades de tratamento da doença renal crônica na população brasileira - Vilela, Pámella Arrais (2025)
Introduction: Chronic Kidney Disease (CKD) is one of the leading causes of mortality, morbidity, and healthcare costs worldwide. Studies indicate that individuals in socially disadvantaged groups have a higher prevalence of CKD and poorer access to quality treatment.Objective: To analyze social inequalities in the prevalence and treatment modalities of CKD in Brazil. Methods: Data from the 2019 National Health Survey (PNS) were used, where participants answered questions about a prior medical diagnosis of CKD (yes or no) and treatment modalities (transplant, medication treatment, hemodialysis, peritoneal dialysis, regular professional monitoring). Inequality stratifiers such as sex, race/ethnicity, education, and area of residence were assessed. Educational inequality in CKD was evaluated using the Slope Index of Inequality (SII), the Relative Index of Inequality (RII), and the Concentration Index (CIX) by sex, race/ethnicity, and area of residence.Results: The prevalence of CKD was 1.49% (95% CI: 1.35–1.63), being higher among women (52.9%), individuals aged 60 years or older (37.0%), and those with low educational levels. All SII and CIX values were negative, indicating higher prevalences of CKD and treatment modalities in disadvantaged groups, except for transplantation. It is noteworthy that CKD prevalence was higher in less educated groups, regardless of sex, race/color, and area of residence. The treatment modalities showed CIX values greater than 20 (transplantation) and lower than -20 (hemodialysis and peritoneal dialysis), indicating significant educational inequality. Virtually all RII values were greater than 1, reinforcing inequality. For CKD diagnosis, SII ranged from -0.69 to -1.90, with the greatest inequalities observed among females, White race/color, and urban residence. CIX ranged from -7.2 to -20.0, with the highest inequalities among males, White race/color, and urban residence. For treatment modalities, SII ranged from 0.02 to -0.75, with medication treatment and regular follow-up with a healthcare professional showing the greatest inequalities. CIX varied between -32.9 and 20.8, with the highest relative inequalities observed for hemodialysis and peritoneal dialysis. Only transplantation had positive SII and CIX values, indicating a higher concentration among the more educated..Conclusion: Absolute and relative educational inequality for CKD was generally higher among less educated women, less educated White individuals, and less educated urban residents. Regarding the observed treatment modalities, while kidney transplantation is more concentrated among the more educated, options such as hemodialysis and peritoneal dialysis are more associated with groups with lower education levels.